Curettage and aspiration in splenic hilar lymph node dissection for spleen-preserving radical D2 gastrectomy - Wang, Wei; Luo, Lijie; Zheng, Yansheng; Wan, Jin (Chinese Journal of Cancer Research; Vol 25, No 4 (August 24, 2013): Chinese Journal of Cancer Research, 2013)
D2 radical gastrectomy is the standard procedure for gastric cancer in the middle or upper part of the stomach. According to the latest Japanese treatment guidelines for gastric cancer, dissection of the splenic hilar lymph nodes is required during the radical treatment for this condition. This study reports a D2 radical total gastrectomy employing the curettage and dissection techniques, in which the resection of the anterior lobe of transverse mesocolon, vascular denudation and splenic hilar lymph node dissection were successfully completed.